The role of the Radiographer in osteoporosis and fracture prevention services – a narrative review. (October 2021) - James, R.; Griffin, J.G.L.; Senior, C.; Love, R.
Abstract: Objective: To explore relevant literature and policy around the role of the radiographer working within osteoporosis services. Discussion will examine the value of radiographers in these services, as well as current limitations and future opportunities for advancing practice in these domains. Key findings: Osteoporosis and fracture prevention are a public health issue that must be addressed to improve patient outcomes following fractures. DXA radiographers currently fulfill an important role in the diagnosis of osteoporosis and collaborative working between radiology and osteoporosis services is to be encouraged. Radiographers are able to extend their role into advanced practice within osteoporosis services such as fracture liaison and rheumatology, they have expert knowledge and experience to bring to these roles and post graduate education can further increase radiographer's expertise in this field. The inability of diagnostic radiographers to become independent prescribers is a current limitation for radiographers working within osteoporosis services. Conclusion: The role of the radiographer working within DXA and osteoporosis services is evolving and is an exciting area of advanced practice. Promoting this specialty within radiography may help to improve job satisfaction as well as recruitment and retention rates. As radiographers scope of practice in osteoporosis changes and evolves, it is hoped that current legislation may change to allow independent prescribing for diagnostic radiographers, which can in turn streamline patient pathways and reduce the burden on primary and secondary care.